Interacting Product and Labor Market Regulation and the Impact of Immigration on Native Wages - Susanne Prantl; Alexandra Spitz-Oener (Institute for the Study of Labor (IZA), 2014)
Does interacting product and labor market regulation alter the impact of immigration on wages of competing native workers? Focusing on the large, sudden and unanticipated wave of migration from East to West Germany after German reunification and allowing for endogenous immigration, we compare native wage reactions across different segments of the West German labor market: one segment without product and labor market regulation, to which standard immigration models best apply, one segment in which product and labor market regulation interact, and one segment covering intermediate groups of workers. We find that the wages of competing native West Germans respond negatively to the large influx of similar East German workers in the segment with almost free firm entry into product markets and weak worker influence on the decision-making of firms. Competing native workers are insulated from such pressure if firm entry regulation interacts with labor market institutions, implying a strong influence of workers on the decision-making of profit-making firms.
Keywords: J61; L50; J3; 330; immigration; product market regulation; labor market regulation